ATIVIDADE ANTIOXIDANTE E TEORES DE FENÓIS, FLAVONOIDES E TANINOS TOTAIS DE Nectandra megapotamica (SPRENG.) MEZ. (LAURACEAE) - DAMIÃO, Pamela Deniz,; GOMES, Paula Fernanda,; SILVA, Ana Francisca Gomes, (ANAIS DO ENIC, 2023)
-